First report of Panstrongylus lignarius (Walker, 1873) (Hemiptera: Reduviidae: Triatominae) in the State of Acre, Brazil - Mariane Albuquerque Lima Ribeiro; Gabriela Vieira de Souza Castro; Janis Lunier de Souza; Acigelda da Silva Cardoso; Fernanda Portela Madeira; Luis Marcelo Aranha Camargo; Dionatas Ulises de Oliveira Meneguetti (Revista da Sociedade Brasileira de Medicina Tropical, 2019)
Abstract INTRODUCTION: This communication reports the first occurrence of Panstrongylus lignarius in the State of Acre, Brazil. METHODS: A specimen of P. lignarius was collected from a residence in a rural area of the municipality of Rio Branco, Acre, Western Amazon. RESULTS: This new report of P. lignarius extends the distribution of this species to eight Brazilian states, and also increases the number of species of Triatominae described from the state of Acre from nine to ten. CONCLUSIONS: The occurrence of P. lignarius deserves attention, since this species has the potential for domiciliation and transmitting Trypanosoma cruzi.